2000
DOI: 10.1207/s15326942dn1802_1
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and Lesion Effects in Brain Activation During Sentence Comprehension and Mental Rotation

Abstract: The development of neurocognitive networks was examined in 2 cognitive paradigms: auditory sentence comprehension and mental rotation of alphanumeric stimuli. Patterns of brain activation were measured with whole brain echoplanar functional magnetic resonance imaging at 3 Tesla in 5 adults (20-28 years old), 7 children (9-12 years old), and 6 pediatric patients (9-12 years old) with perinatal strokes or periventricular hemorrhages. Healthy children and adults activated similar neurocognitive networks, but ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
63
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 59 publications
11
63
0
1
Order By: Relevance
“…Similar brain areas were activated in children and adults as reported earlier by Booth et al (1999Booth et al ( , 2000. Among those, the IPS is known to be a core region involved in mental rotation (Alivisatos and Petrides, 1997;Carpenter et al, 1999;Harris et al, 2000;Harris and Miniussi, 2003;Jordan et al, 2002;Kosslyn et al, 1998;Richter et al, 1997;Tagaris et al, 1996Tagaris et al, , 1998Vingerhoets et al, 2001).…”
Section: Brain Developmentsupporting
confidence: 73%
See 2 more Smart Citations
“…Similar brain areas were activated in children and adults as reported earlier by Booth et al (1999Booth et al ( , 2000. Among those, the IPS is known to be a core region involved in mental rotation (Alivisatos and Petrides, 1997;Carpenter et al, 1999;Harris et al, 2000;Harris and Miniussi, 2003;Jordan et al, 2002;Kosslyn et al, 1998;Richter et al, 1997;Tagaris et al, 1996Tagaris et al, , 1998Vingerhoets et al, 2001).…”
Section: Brain Developmentsupporting
confidence: 73%
“…Results showed that healthy children and adults activate similar brain areas, but there were differences in the distribution of activation across these networks. Adults showed more activation in the superior parietal and middle frontal areas and less activation in the supramarginal gyrus (Booth et al, 2000). In children, the inferior parietal lobe was more active in the right hemisphere, whereas activation in the superior parietal lobe was more lateralized in the left hemisphere (Booth et al, 1999).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Diverse mental rotation measures have produced consistently robust parietal activation and shown marked sensitivity to parietal damage in both adults (44)(45)(46) and children (47).…”
Section: Methodsmentioning
confidence: 99%
“…Π’ Π½Π°ΡˆΠΈΡ… ΠΏΡ€Π΅Π΄Ρ‹Π΄ΡƒΡ‰ΠΈΡ… публикациях Π±Ρ‹Π»ΠΎ ΠΏΡ€ΠΎΠ΄Π΅-монстрировано, Ρ‡Ρ‚ΠΎ Ρƒ Π΄Π΅Ρ‚Π΅ΠΉ младшСго школьного возраста процСсс ΠΏΠΎΠ½ΠΈΠΌΠ°-ния Π›Π“Πš тСсно связан с ΡƒΡ€ΠΎΠ²Π½Π΅ΠΌ Ρ€Π°Π·Π²ΠΈ-тия сСрийной ΠΎΡ€Π³Π°Π½ΠΈΠ·Π°Ρ†ΠΈΠΈ Ρ€Π΅Ρ‡ΠΈ. Мно-гочислСнныС Π½Π΅ΠΉΡ€ΠΎΠ²ΠΈΠ·ΡƒΠ°Π»ΠΈΠ·Π°Ρ†ΠΈΠΎΠ½Π½Ρ‹Π΅ исслСдования (Π² Ρ‚ΠΎΠΌ числС, Π΄Π΅Ρ‚Π΅ΠΉ) ΠΏΠΎ-ΠΊΠ°Π·Π°Π»ΠΈ, Ρ‡Ρ‚ΠΎ ΠΏΠΎΠ½ΠΈΠΌΠ°Π½ΠΈΠ΅ грамматичСски слоТных ΠΏΡ€Π΅Π΄Π»ΠΎΠΆΠ΅Π½ΠΈΠΉ Π²Ρ‹Π·Ρ‹Π²Π°Π΅Ρ‚ ΠΏΠΎΠ²Ρ‹-ΡˆΠ΅Π½Π½ΡƒΡŽ Π°ΠΊΡ‚ΠΈΠ²Π°Ρ†ΠΈΡŽ Π·ΠΎΠ½, располоТСн-Π½Ρ‹Ρ… ΠΈ Π² ΠΏΠ΅Ρ€Π΅Π΄Π½ΠΈΡ… ΠΎΡ‚Π΄Π΅Π»Π°Ρ… ΠΌΠΎΠ·Π³Π° (44 ΠΈ 45 поля ΠΏΠΎ Π‘Ρ€ΠΎΠ΄ΠΌΠ°Π½Ρƒ, прСмоторная ΠΊΠΎΡ€Π°), ΠΈ Π² Π·Π°Π΄Π½ΠΈΡ… (задняя Ρ‚Ρ€Π΅Ρ‚ΡŒ Π²Π΅Ρ€Ρ…Π½Π΅ΠΉ Π²ΠΈ-сочной ΠΈΠ·Π²ΠΈΠ»ΠΈΠ½Ρ‹, задняя Ρ‡Π°ΡΡ‚ΡŒ Π²Π΅Ρ€Ρ…Π½Π΅ΠΉ височной Π±ΠΎΡ€ΠΎΠ·Π΄Ρ‹, угловая ΠΈ Π½Π°Π΄ΠΊΡ€Π°Π΅-вая ΠΈΠ·Π²ΠΈΠ»ΠΈΠ½Ρ‹, пСрСдняя Ρ‚Ρ€Π΅Ρ‚ΡŒ срСднСй височной ΠΈΠ·Π²ΠΈΠ»ΠΈΠ½Ρ‹) 1996, Caplan et al;1999, Booth et al, 2000Kaan, Swaab, 2002;BenSchachar et al 2004;Grodzinsky, 2006;Rodd et al, 2010;Yeatman et al, 2010;Den Ouden et al, 2012).…”
unclassified